MULTICRITERION MODEL OF AN AIR CARGO TERMINAL TECHNOLOGICAL AND PLANNING DECISION OPTIMIZATION - Ivannikova, Viktoriia (Proceedings of National Aviation University, 2013)
Developed multicriterion economic and mathematical model to solve the technological and planning decision optimization problem for Air Cargo Terminal is presented in the article. The algorithm of the multicriterion Air Cargo Terminal parametrization problem solution has been formulated.